Characterization Of Oil Retrogression Of Aluminum Alloy 7075 - Ng, Guan Yao (2014)
Aluminum alloy 7075 is a useful industrial material thanks to its high strength to weight ratio. However, it is susceptible to corrosion due to numerous constituent particles with various electrochemical potentials the combination of which leads to susceptibility to corrosion. This issue was solved by using overage treatment with the penalty of 10-15% of peak strength. Previous research found that retrogression and re-aging (RRA) heat treatment improves corrosion resistance while maintaining the strength of the alloy. In this research, the retrogression process was studied to a greater extend with oil as the heating medium in relation to the standard retrogression. The tensile specimens are peak aged before retrogressed at 165oC, 185oC, and 205oC for 10 and 30 minutes in oil and standard furnace followed by re-aging at 120oC for 24 hours. Next, the specimens were put through tensile test, hardness test, Tafel DC corrosion test, and microstructure characterization by using Scanning Electron Microscope (SEM). The result of the analysis showed the mechanical properties of the alloy to decrease with increasing retrogression temperature and time for both oil and standard retrogression due to the increase in incoherent ɳ phase volume fraction as observed under the SEM analysis. In comparison between oil and standard retrogression, oil retrogression out-performed standard retrogression at 165 °C for 10 minutes with better corrosion resistance at corrosion current density of 6.64 μA/cm2 and tensile strength of 632.73 MPa.